EFFECT OF DIFFERENT BINDER MATERIAL ON THE QUALITY OF FRESHWATER MUSSEL (Pilsbryoconcha sp.) MEATBALLS DURING COLD TEMPERATURE STORAGE (± 5 °C) - Dian Iriani; Lucky Meliana Manurung; Syahrul Syahrul (Berkala Perikanan Terubuk, 2019)
Kijing is a freshwater mussel which contains high nutritional value, but its use is only as a biofilter in the water, as well as durian seeds and jackfruit seeds which are just thrown away. The purpose of this study was to determine the effect of using different binders on organoleptic and folding test quality of freshwater mussel meatballs during cold temperature storage (± 5 °C). The experimental design used in this study was a Non Factorial Randomized Block Design (RBD), namely the addition of different binders (tapioca, durian seed, and jackfruit seed flour) in the manufacture of freshwater mussel meatballs, which consisted of five levels of treatment namely B0 (75g + 0g + 0g), B1 (55g + 10g + 10g), B2 (35g + 20g + 20g), B3 (15g + 30g + 30g), B4 (0g + 37.5g + 37.5g), respectively. The group or replication in this study was the length of storage consisting of 0 days (H0), 5 days (H5), 10 days (H10), 15 days (H15). The results showed that the use of different binding materials had a significant effect on organoleptic quality (appearance, aroma, taste, texture), and folding test of freshwater mussel meatballs during cold storage (± 5 °C). Based on the test parameters indicate that B2 was the best treatment for 10 days of cold temperature storage (± 5 °C), with the results of organoleptic tested, namely the value of appearance (7.2) with brilliant criteria, intact, and brownish white; aroma value (8.0) which was typical of freshwater mussel meat, specific spices, a little aroma of durian and jackfruit seed starch; taste value (7.4) which was tasty, typical of freshwater mussel meat, a little taste of durian and jackfruit seed starch; texture value (7.9) which was springy, solid, not brittle; while the folding tested value (40) was not cracked if folded by a quarter circle.